Analisis Tingkat Pencemaran Airtanah Akibat Limbah Vinasse berdasarkan Metode Indeks Pencemaran di Padukuhan Mrisi Kalurahan Tirtonirmolo Kapanewon Kasihan Kabupaten Bantul Daerah Istimewa Yogyakarta - Erinda, Evi; Widiarti, Ika Wahyuning (Jurnal Lingkungan Kebumian Indonesia, 2023)
Waste resulting from alcohol production is called liquid vinasse. Characteristic of vinasse has a high temperature (80OC), has an acidic pH (2-4.5), blackish color, strong odor, and is corrosive. In producing 1 L of alcohol produces 15 L of liquid vinasse. Some of this waste is processed as liquid fertilizer, but the other part is still not managed and is thrown into the environment and ends up in Anak Kali Bedog. The aim of this research is to analyze the level of groundwater pollution using the Pollution Index Method for the parameters pH, TDS, BOD, COD and Sulfide. The sampling method used in this research is Purposive Sampling based on consideration of the distance of the well to irrigation of vinasse and the direction of groundwater flow. Laboratory analysis methods are carried out to determine the quality of groundwater regarding the parameters pH, TDS, BOD, COD and Sulfide. Samples were taken from 10 well water points and 1 water point from an irrigation outlet vinasse. The results of groundwater quality status analysis using the pollution index method show that the research area has 2 pollution classes, namely lightly polluted with an IP value of 2.7332-3.3640 and moderately polluted with an IP value of 5.1088-5.7014